Petrus Bentzmann Consul Primariae Civitatis Gedanensis Nat. M.DC.XVI. Den. At. M.DC.XCIII. / Leonard Heckenauer. - Heckenauer, Leonhard (165.-1704?) (1693)
Przedstawia portret w popiersiu w obramieniu architektonicznym Peter Bentzmann.